Mental health of immigrants from the former Soviet Bloc: a future problem for primary health care in the enlarged European Union? A cross-sectional study - Sundquist Jan; Johansson Sven-Erik; Blomstedt Yulia (BMC, 2007)
Abstract Background Enlargement of the European Union has caused worries about the possibility of increased migration from its new members, the former Soviet countries, and consequently increased demands on the health care systems of the host countries. This study investigated whether or not earlier immigrants from the former Soviet Bloc have poorer self-reported mental health, measured as self-reported psychiatric illness and psychosomatic complaints, than the host population in Sweden. It also examined the particular factors which might determine the self-reported mental health of these immigrants. Methods The cross-sectional national sample included 25-84-year-old Swedish-born persons (n = 35,459) and immigrants from Poland (n = 161), other East European countries (n = 164), and the former Soviet Union (n = 60) who arrived in Sweden after 1944 and were interviewed during 1994-2001. Unconditional multivariate logistic regression was used in the analyses. Results The findings indicated that the country of birth had a profound influence on self-reported mental health. Polish and other East European immigrants in general had a twofold higher odds ratio of reporting psychiatric illness and psychosomatic complaints, which fact could not be explained by adjustments for the demographic and socioeconomic variables. However, immigrants from the former Soviet Union had odds similar to those of the Swedish-born reference group. Adjustments for migration-related variables (language spoken at home and years in Sweden) changed the association between the country of birth and the outcomes only to a limited extent. Conclusion Since poor mental health may hinder acculturation, the mental health of immigrants from Poland and other East European countries should be acknowledged, particularly with the expansion of the European Union and inclusion of nine former Soviet Bloc countries by 2007.